2021
DOI: 10.1038/s41598-021-91100-x
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of PEDOT-rGO/HKUST-1 for high performance symmetrical supercapacitor device

Abstract: A novel poly(3,4-ethylenedioxythiophene)-reduced graphene oxide/copper-based metal–organic framework (PrGO/HKUST-1) has been successfully fabricated by incorporating electrochemically synthesized poly(3,4-ethylenedioxythiophene)-reduced graphene oxide (PrGO) and hydrothermally synthesized copper-based metal–organic framework (HKUST-1). The field emission scanning microscopy (FESEM) and elemental mapping analysis revealed an even distribution of poly(3,4-ethylenedioxythiophene) (PEDOT), reduced graphene oxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…The XRD pattern of the composite shows a single prominent peak corresponding to silica along with some small peaks corresponding to HKUST‐1 suggesting that the surface of HKUST‐1 is nearly completely covered by silica. The peaks of HKUST‐1 were in well accordance with the previous study by Mohanadas et al., (2021) [37] and broad peak for SiO 2 matched well with previous report by Purwaningsih et al., (2018) [38] …”
Section: Resultssupporting
confidence: 92%
“…The XRD pattern of the composite shows a single prominent peak corresponding to silica along with some small peaks corresponding to HKUST‐1 suggesting that the surface of HKUST‐1 is nearly completely covered by silica. The peaks of HKUST‐1 were in well accordance with the previous study by Mohanadas et al., (2021) [37] and broad peak for SiO 2 matched well with previous report by Purwaningsih et al., (2018) [38] …”
Section: Resultssupporting
confidence: 92%
“…[ 34 ] The GO diffraction peaks overlap around the 2 θ angle of 9.8°, and a typical polymer composite reflection is also observed at ≈25.6°. [ 35 ] The XRD results for the copper chelate composite film indicate there are weak interaction peaks at 2 θ angles of 10.3° and 25°, which suggest the coordination of copper chelates with the TREN:PEDOT/GO polymer composite. The remaining sharp diffraction peaks, particularly at 2 θ = 32.1°, 35.3°, 38.7°, and 52.7°, correspond to CuO peaks at (110), (111), (200), and (202) (JCPDS NO.89‐2529), indicating a well‐crystallized tenorite structure.…”
Section: Resultsmentioning
confidence: 99%
“…The micrographs clearly show that HHAC is made up of an interconnected porous sheet-like structure with a network of voids all over the surface (Figure S2 of the Supporting Information). By serving as ion-buffering reservoirs, this network of voids improves the material’s electrochemical performance. , The hydrothermal treatment followed by KOH activation at high temperature is primarily responsible for the HHAC sample’s sheet-like structure. Furthermore, HHAC/PPy micrographs demonstrated that PPy is present in a globular shape across the HHAC sheet matrix which acts as a cushion for the PPy globules (Figure a–c).…”
Section: Resultsmentioning
confidence: 99%